Persepsi orang cina terhadap Islam Hadhari - Mohd Ridhuan Tee Abdullah, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
Islam is a misunderstood religion. The negative impression towards Islam accumulated through negative behaviour and political socialization process. Hence, Islam is labeled as a negative religion which is synonym with fighting each other, disunity, dirty, poor, aggressive, harsh, killing each other etc. Muslims can’t really put the blame on the Non-Muslims because of their prejudices. All these things happened because we failed to potrait a good image after the collapse of the Islamic empire during the First World War. We only can be proud of the past and failed to create a present glory. Whatever glory we had in the past is nowhere to be seen nowadays. What is happening now makes it difficult for the Muslims to propagate Islam to the Non-Muslims. If we look at the 10 principles of Islam Hadhari, it possess great values and acceptable to the Non- Muslims. Those principles are also included in the teachings of Confucious and Buddhism. However, these good teachings are not given due attention but rather manipulated and politicized. PAS produces books against the concept while UMNO on the other hand try its very best to defend it. These leads to great confusion among the Non-Muslims.